Phenological, morpho-physiological and root characteristics in relation to productivity of wheat genotypes under early and late heat conditions - S.V, Sai Prasad; Saxena, D. C.; Chatrath, R.; Mishra, S.C.; Watt, M.; Wasan, A.; Parashar, R.; Gautam, A.; Rathi, I. (Annals of Agricultural Research, 2016)
Various phenophases of wheat crop are subjected to different and wide range of temperature spell. Early heat and late or terminal heat conditions have been limiting the wheat productivity and production. Forty wheat genotypes were screened for grain yield in the field under early heat/ early sown (Oct. last week sown) and late heat (December first week sown) conditions. Based on the yield potential, five high yielding and five low yielding varieties were selected to study morphophysiological traits and root characteristics in relation to grain yield under early and late sown conditions. For early sown conditions, the high yielding genotypes included HI 1531, HD 4672, C 306, HW 2004 and HD 2888, whereas, the low yielding genotypes were HS 277, UP 2338, DBW 17, NIAW 34 and DBW 16. For late sown conditions, the high yielding genotypes included HI 8627, HD 4672, C 306, NI 5439 and HUW 234, while, the low yielding genotypes were HS 277, DBW 16, VL 829, UP 2338 and A 9-30-1. High yielding genotypes exhibited early germination, early heading and high canopy temperature depression (CTD) values under early sown conditions. The relative water content (RWC) was found to be high in high yielding genotypes under both the growing conditions, maintaining the higher water potential. Under early sown conditions, high yielding genotypes showed higher number of tillers/plant,Â  number of ears/plant, biomass, grain yield and harvest index, whereas, under late sown or terminal heat conditions, high yielding genotypes exhibited lesser number of tillers/plant and number of ears/plant. It was observed that under early sown conditions, the high yielding genotypes had lesser root weight but higher root length and root density in deeper soil depths, compared to low yielding genotypes. In contrast, under late sown conditions the high yielding genotypes possessed more root weight and density in upper soil depths compared to low yielding genotypes.